Habitat Use, Feeding Behaviour and Conservation Threats of Black-Necked Cranes at Gangtey-Phobji Valley, Wangdue Phodrang, Bhutan - Dorji, Gyeltshen; Dorji, Ugyen (International Journal of Environment, 2021)
Black-necked Cranes are revered as sacred birds and are considered the epitome in their biological range. They function as an umbrella species in terms of ecology ensuring that biodiversity is protected across a wider range of habitats. The study was carried out at Gangtey-Phobji valley to determine the habitat use, feeding behaviour and conservation threats of the Black-necked crane. Stratified non-random sampling was used and plot sizes of 1 x 1 m2 for herbs and 5 x 5 m2 for shrubs were used for determining the habitat use and feeding behaviour. To understand the conservation threats, a total of 129 households were surveyed. PC-ORD software was used for cluster analysis and to compute the indicator species of the habitat. A total of 50 herbs and 10 shrubs belonging to 37 families were recorded from the study area. Yushania microphylla, Juncus chrysocarpus, Rosa sericea and Rhododendron thomsonii were the indicator species of the preferred habitat. The peak flying hours were at around 08:00 a.m. and 05:00 p.m. The foraging was intensive from 09:00 a.m. to 11:00 a.m. and 03:00 p.m. to 04:00 p.m. The social (31%) and natural (31%) threats were found to be the most serious threats, followed by political threats (30%). Habitat degradation triggered by anthropogenic activities was the main threat. The cranes preferred the artificial roosts over natural ones recommending more artificial roosts for its conservation. The protection of habitats by limiting the farm road within the habitat, managing waste and stray dogs were deemed crucial.